The synthesis of aryl halomethylated unsaturated iminolactones - Zonouzi, Afsaneh; Rahmani, Hossein; Biniaza, Mojtaba; Izakiana, Zakieh; Ng, Seik Weng (SAGE Publications, 2011)
Halomethylated iminolactones have been synthesised from alkyl isocyanides, acetylene dicarboxylic acid esters and halogenated acetophenones in solvent free microwave assisted multi-component reactions.